Folate, homocysteine and selected vitamins and minerals status in infertile women. (2nd January 2017) - La Vecchia, Irene; Paffoni, Alessio; Castiglioni, Marta; Ferrari, Stefania; Bortolus, Renata; Ferraris Fusarini, Chiara; Bettinardi, Nora; Somigliana, Edgardo; Parazzini, Fabio
Abstract: Objectives: Diet has been recognised as a crucial factor influencing fetal and maternal health. Adequate levels of substances such as homocysteine, folate and vitamin B12 have been associated with a higher rate of success in infertility treatments. Few data, however, are available on the average levels of micronutrients in the blood of reproductive-aged women, and specific values for adequate levels are not available. The aim of this cross-sectional study was to measure levels of folate, homocysteine and selected vitamins and minerals in women attending the infertility unit of an academic hospital for in vitro fertilisation (IVF). Methods: Fasting venous blood samples were taken in the morning during routine screening before IVF in order to measure: serum folate, red blood cell (RBC) folate, total plasma homocysteine, vitamin B12, vitamin A, vitamin E, serum iron and serum ferritin. Results: Among 269 women aged 37 ± 4 years, only 69% and 44% showed adequate levels of homocysteine and vitamin B12, respectively. Serum folate was appropriate in 78% of the study participants, but only a minority (12%) had a concentration of RBC folate regarded as optimal for the prevention of fetal neural tube defects. Serum levels of vitamin A, vitamin E, iron and ferritin were, however, appropriate in the vast majority of participants (>80%). Conclusion: Folate levels were largely inadequate among women attending an infertility clinic for IVF. Vitamin B12 levels were also found to be inadequate.